ANALISIS REAKSI PASAR SEBELUM DAN SESUDAH PELANTIKAN KABINET INDONESIA MAJU PADA PERUSAHAAN BUMN DI BURSA EFEK INDONESIA - Kango, Abdullah; Saerang, Ivonne S.; Mangantar, Maryan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
President Joko Widodo had been inaugurated ministers in the Advanced Indonesia Cabinet that will help him to undergo the wheels of government in the 2019-2024 period on October 23, 2019. The inauguration is one of the important event in the capital market shows that there are some reactions of the event. The aims of this study to see how the reaction of capital market by looking at the differences of the variabels abnormal return, trading volume activity and trading frequency of stock before and after the event. The research object is 20 companies of state-owned corporation on period during Septemberâ€“November 2019. The analytical method used to test is compares two means from each variables. The observation period is 14 days which is 7 days before and 7 days after event. This hypothesis test used paired sample t-test analysis. The result of this research shows that there is significant differences between abnormal return before and after of event, there is no significant differences between trading volume activity before and after of event, and there is a significant differences between trading frequency before and after event.Â Keywords: Event Study, Abnormal Return, Trading Volume Activity, Frequency of Stock Trading